Low cross-neutralization of hepatitis C correlates with liver disease in immunocompromized patients. (1st June 2015) - Maurin, Guillemette; Halgand, Boris; Bruscella, Patrice; Fresquet, Judith; Duclos-Vallée, Jean-Charles; Roque-Afonso, Anne-Marie; Cosset, François-Loïc; Samuel, Didier; Lavillette, Dimitri; Féray, Cyrille
Abstract : Background and aims: Chronic hepatitis C virus (HCV) infection causes severe liver disease in HIV-infected patients and liver transplant recipients. The impact of serum and immunoglobulin on viral entry was analysed in these patients. Method: Sera from 60 anti-HCV positive patients, including 30 who were also anti-HIV positive, were tested with HCVpp from different genotypes (1a, 1b, 3 and 4) and with HCVcc (H77/JFH1). Seventeen HIV-seropositive and 13 HIV-seronegative patients with decompensated liver disease were studied before and after liver transplant. Results: Serum neutralization was markedly lower after liver transplant and in HIV patients than in mono-infected immune-competent individuals. This effect was due to low antibody-mediated neutralization. In HIV patients, low neutralization was correlated with low lymphocyte T CD4 + cell counts and the severity of liver disease. To characterize neutralization, we tested HCVpp lacking hypervariable region (HVR1) and SR-BI receptor cholesterol transfer inhibition by BLT-4. These experiments showed that neutralization was strongly dependent on the HVR1 and the SR-BI receptor. HVR1 sequences showed that selective pressures were low in immune-compromised patients and highly correlated to HCV neutralization after liver transplant. Neutralization experiments were reproduced with HCV strain JFH1. Conclusion: Serum neutralization in HIV-coinfected patients and HCV-infected liver transplant recipients is poor enhancing HCV entry through HVR1/SR-BI interplay. This may contribute to the severity of hepatitis C in these settings. Abstract : Supplemental Digital Content is available in the text